Why consumers choose green? The roles of environmental sensitivity, health consciousness, and attitude - Fitroh Adhilla; Rai Rake Setyawan; Emmy Oresca Menes (Universitas Ahmad Dahlan, 2026)
Green purchase intention is largely shaped by psychological factors that influence how consumers perceive and evaluate environmental issues. The present study investigates how environmental sensitivity and health consciousness drive the emergence of green purchase intention, while considering attitude toward green products as an intervening variable. The study was conducted among Avoskin consumers in Indonesia, and 152 participants were selected through purposive sampling. The analysis employed SmartPLS to assess measurement validity, construct reliability, and hypotheses. Empirical evidence demonstrates that environmental sensitivity and health consciousness significantly contribute to the development of attitudes toward green products and green purchase intention. Moreover, these attitudes directly influence green purchase intention. Attitude toward green products mediates the relationship between environmental sensitivity and health consciousness and green purchase intention. This study extends the theory of planned behavior and the value-belief-norm theory within the clean beauty industry in an emerging market. By validating the intervening role of green attitudes, the research clarifies the cognitive mechanism through which abstract psychological traits (environmental sensitivity and health consciousness) translate into concrete behavioral intent. For eco-friendly brands like Avoskin, these findings offer a blueprint for targeted marketing strategies. Marketing campaigns should simultaneously emphasize ecological benefits and personal health advantages, such as non-toxic ingredients or skin safety.